Seismic hazard assessment of Kuala Lumpur, Malaysia due to long distant Sumatran megathrust earthquakes based on a comparative study on ground-motion prediction equations - Adnan, Azlan (2015)
This paper has classified four spectral ground-motion prediction equations (GMPEs) derived for subduction interface earthquakes through a comparative study based on the several main Sumatran earthquakes data recorded in Peninsular Malaysia. The goal of classification was to identify the GMPEs that were more favorable to be used for the region. The predicted acceleration response spectra by the relations provided by Zhao et al. (2006) and Megawati and Pan (2010) were found to correlate well approximately, with the recorded spectra. The seismic hazard of Kuala Lumpur, Malaysia was assessed deterministically by calculating the acceleration response spectra caused by three long distant Sumatran megathrust earthquakes (the worst possible earthquake scenarios) using the favorable spectral GMPEs. Current building code (BS8110) in the region requires that buildings should be capable of resisting a notional ultimate lateral design load equals to 1.5% of the characteristic dead weight of the structure, simultaneously applied at each floor. The results show that the risk level for buildings of the city with natural period Tn = 1.5s corresponded to 15-story buildings located on rock sites (Eurocode 8 (EC8) soil type A) is remarkably high. It was due to the relatively high demand spectrum due to a worst possible earthquake scenario with moment magnitude (MW) 9.3 and hypocentral distance (Rhypo) of 530 km from Kuala Lumpur compared to the minimum design level of 0.015g.